Unionism and the Job Attachment of Canadian Workers - Swidinsky, Robert (Relations industrielles / Industrial Relations, 1992)
The analysis in this paper is based on the 1986-87 Labour Market Activity Survey (LMAS) longitudinal data made available by Statistics Canada. It presents evidence of the effect of unionism on job tenure and job separation rates derived from regressions which control for the effects of wages, pension rights, firm size and other factors. Job separations and job tenure provide different perspectives of job attachment in that the former represents decision-making at a single point in time whereas the latter over extended periods. This paper also addresses the questions of bias inherent in selectivity and the simultaneous determination of wages and tenure.